Dual Role of WISP1 in maintaining glioma stem cells and tumor-supportive macrophages in glioblastoma - Weiwei Tao (Nature Portfolio, 2020)
The tumour microenvironment plays an important role in promoting glioblastoma. Here, the authors show that glioma stem cells secrete WISP1, which promotes both the survival of the stem cells and tumour-associated macrophages.